PREDIKSI WHISTLEBLOWING: PERAN ETIKA, FAKTOR ORGANISASIONAL DAN FAKTOR KONTEKSTUAL - Priyastiwi Priyastiwi (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2016)
This paper seeks to identify and discusses the factors that affect an organization’s internal whistleblowing intentions related to ethics. This paper integrates theindividual variable which are ethical judgment and the intensity of the moral; organizational variable that support the organizations; and situational variables, such as the status of wrongdoers, the possibility of retaliation, and tolerance of dissent;that is expressed in a group of theoretical propositions, which is used to develop a frame of thoughts in the study. This paper attempts to provide useful knowledges on how individuals form the intention of reporting and how ethical values can affect these intentions, thus, itwill be able to provide a contribution for a further understanding of the phenomena associated with an ethical whistleblowing.The purpose of this paper is to provide a general discussion about the decision-making process of internal whistleblowing along with an overview of the ethical element that is reflected in the psychological, situational and organizational characteristics. Through a theoretical model, based on the existing literature, it indicates that whistleblowing is a very complex phenomenon resulted from an interaction of situational, organizational and individualfactors. The complexity of the phenomenon depends not only on the various factors that affect whistleblowing, but also related to the attitudes toward the ethical judgment and moral intensity. Whistleblowing behavior is embedded in a social context, so it can vary according to the values, beliefs and certain social norms. Factors that may inhibit the whistleblowingbehavioris a violation of the personal relationship between employee and employer, aversion to conflict, and interpersonal relations. The passivity of the employees can weaken the relationship between whistleblowing attitudes andwhistleblowingintentions, therefore,it causes the observer to not disclose the information.Specifically, organizations must improve the legitimacy of an internal whistleblowing and take actions that can reduce the fear of retaliation, increase the perceived support and easily identify the actions and behaviors that must be reported. By expanding the knowledge of the phenomenon and discussing the aspects and its implications, hence, it may encourage any debates on the topic and encourage organizations to rethink their policies and strategies for whistleblowing decision making.